2017
DOI: 10.1016/j.cortex.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the development of agrammatic aphasia: A tensor-based morphometry study

Abstract: Agrammatic aphasia can be observed in neurodegenerative disorders and has been traditionally linked with damage to Broca’s area, although there have been disagreements concerning whether damage to Broca’s area is necessary or sufficient for the development of agrammatism. We aimed to investigate the neuroanatomical correlates of the emergence of agrammatic aphasia utilizing a unique cohort of patients with primary progressive apraxia of speech (PPAOS) that did not have agrammatism at baseline but developed agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…The fact that Broca’s area showed abnormalities before the development of agrammatic aphasia in DY suggests that involvement of this region could be a useful predictor for the future development of aphasia in PPAOS. We have previously shown this to also be the case in a larger cohort of patients with PPAOS(Whitwell, et al, 2017). Over time we observed progression in these regions but also the gradual involvement of other regions, starting with the motor cortex, lateral temporal lobe and thalamus in 2013, and then with later involvement of sensory cortex and parietal lobes in 2015.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The fact that Broca’s area showed abnormalities before the development of agrammatic aphasia in DY suggests that involvement of this region could be a useful predictor for the future development of aphasia in PPAOS. We have previously shown this to also be the case in a larger cohort of patients with PPAOS(Whitwell, et al, 2017). Over time we observed progression in these regions but also the gradual involvement of other regions, starting with the motor cortex, lateral temporal lobe and thalamus in 2013, and then with later involvement of sensory cortex and parietal lobes in 2015.…”
Section: Resultssupporting
confidence: 56%
“…We have previously reported longitudinal data over a two year interval in patients with PPAOS in order to investigate patterns of disease progression(Whitwell et al, 2017; Zalewski et al, 2014). We showed that some patients maintained an isolated AOS over time, while some developed agrammatic aphasia, and others developed parkinsonian and other features akin to progressive supranuclear palsy and corticobasal syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…However, agPPA showed faster rates of atrophy in the inferior frontal lobe compared to PPAOS, reflecting greater decline in agrammatism than the PPAOS patients 11 . Agrammatism can develop over time in some PPAOS patients, although not all, and when it does develop it is associated with atrophy of the left inferior frontal lobe, thalamus and putamen, showing that a network of regions is responsible for the development of agrammatic aphasia 186 .…”
Section: Agrammatic Primary Progressive Aphasia and Primary Progressimentioning
confidence: 99%
“…This pattern differs from agPPA, with agPPA showing more widespread involvement of the frontal and temporal lobes (Josephs et al, 2013). Longitudinal neuroimaging has been described in PPAOS, with grey matter atrophy spreading from the initial focal premotor pattern into the prefrontal and motor cortices, in addition to the basal ganglia and midbrain (Josephs et al, 2014;Whitwell et al, 2017). However, it is unknown how these longitudinal patterns of atrophy compare to those observed in agPPA, and whether the syndromes remain relatively distinct on neuroimaging as the diseases progress or whether they converge into similar patterns of progression, especially given that PPAOS subjects can develop agrammatism over time (Josephs et al, 2014;Whitwell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%